PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN WORD OF MOUTH TERHADAP KEPUASAN PASIEN DI KLINIK HARAPAN SEHAT JATISARONO, NANGGULAN, KULON PROGO: PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN WORD OF MOUTH TERHADAP KEPUASAN PASIEN DI KLINIK HARAPAN SEHAT JATISARONO, NANGGULAN, KULON PROGO - Wiraswati, Ananda; Sumarni, Murti; Basri, Anindita Imam (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2021)
The research is aimed at recognizing the effect that the quality of service, facilities, word of mouth can have on patients’ satisfication at the Health Care Clinic, Nanggulan, Kulon Progo. The method of colecting data on this study uses interviews, observations, and questionnairies by non probability sampling techniques of 80 respondents and data analysis using t, test F, and liniear regression. Based on the results of the study, regression equations are obtained as follows: Y=0,714 + 0,254 (X1) + 0,124 (X2) + 0,583 (X3). Research shows that the quality of service, facilities, and word of mouth, have a positive and significant impact on the patient’s satisfication. Simultaneously demonstrated that the quality of service, facilities, and word of mouth are significant to the patient’s satisfication. Studies of the three independent variables jointly affected the patient’s satisfication. Coefficient determinations in this study are 0,627 or 62,7 %.